Role of biomarkers in risk stratification of acute coronary syndrome - Nagesh, C.M. (Medknow Publications, 2010)
Diagnosis of acute coronary syndrome (ACS) encompasses a wide spectrum of myocardial ischaemia varying from assuredly benign to potentially fatal. Cardiac biomarkers have had a major impact on the management of this disease and are now the cornerstone in its diagnosis and prognosis. In this review we discuss both the established and the newer emerging biomarkers in ACS and their role in highlighting not only myocardial necrosis but also different facets of the pathophysiology of ACS. The future of cardiac biomarker testing may be in multimarker testing to better characterize each patient of ACS and thus tailor both short-term and long-term therapy accordingly. This novel concept, however, needs to be tested in clinical trials for its incremental value and cost-effectiveness.